2010
DOI: 10.1111/j.1365-2761.2009.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in genes between a high virulence strain G4 and a low virulence strain G18 of Flavobacterium columnare by using suppression subtractive hybridization

Abstract: Flavobacterium columnare is the causative agent of columnaris disease. Different genetic groups of F. columnare show to some extent different degrees of virulence. To identify genetic differences between the high virulence strain G(4) and the low virulence strain G(18) of F. columnare, suppression subtractive hybridization was used. A total of 46 genes were identified from the virulent strain G(4), 35 of which showed some degree of homology with known proteins and can be classified into 11 categories: DNA repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As an important component of the iron uptake system, several TonB-dependent receptors were reported to have relevance in pathogen pathogenicity (Alvarez et al 2008, Tauseef et al 2011. In a comparative study of Flavobacterium columnare strains with high and low virulence, Li et al (2010) identified 3 tdr genes in the high virulence strain but not in the low virulence strain. In a study of Bordetella pertussis, inactivation of a TonB-dependent receptor gene, fauA, was found to have a profound impact on in vivo growth and survival (Brickman & Armstrong 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As an important component of the iron uptake system, several TonB-dependent receptors were reported to have relevance in pathogen pathogenicity (Alvarez et al 2008, Tauseef et al 2011. In a comparative study of Flavobacterium columnare strains with high and low virulence, Li et al (2010) identified 3 tdr genes in the high virulence strain but not in the low virulence strain. In a study of Bordetella pertussis, inactivation of a TonB-dependent receptor gene, fauA, was found to have a profound impact on in vivo growth and survival (Brickman & Armstrong 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies using subtractive hybridization documented variation in transcripts related to iron transport between two F. columnare strains with different virulence levels in grass carp (Li et al . ). More recently, one study identified the presence of iron uptake machinery, determined that iron levels in media were found to be crucial for growth in vitro , and found that F. columnare can synthesize siderophores which chelate and facilitate iron uptake (Guan et al .…”
Section: Introductionmentioning
confidence: 97%
“…For example, in low‐iron conditions, E. coli will synthesize outer membrane proteins for upregulation and Pseudomonas fluorescens will increase TonB‐dependent OMR (TdrA; Hu et al., 2012; Sigel & Payne, 1982). The outer membrane proteins and TonB‐dependent receptors are targets for new antibiotic therapies, and changes to these proteins may lead to avirulent pathogens (Li et al., 2010; Moeck & Coulton, 2002).…”
Section: Introductionmentioning
confidence: 99%